Efeito de diferentes níveis de feno de leucena (Leucaena leucocephala (LAM.) de Wit) sobre o crescimento de ovinos em confinamento - Gurgel, Milton Alves (1986)
The objetive of this research was to evaluate the effect of different levels of leucena hay on the growing of sheeps raised under confinement. The following parameters were measured: feed consumption, weight gain, feed conversion and carcass yield [...]